Indigenous Technical Know how of Coastal Fisher folk of Sindhudurg district in Maharashtra - H. Vivek Nirmale; S. Bharat Sontakki; R.S. Biradar (Journal of Agricultural Extension Management, 2025)
Indigenous knowledge is the knowledge that people in a given community have developed over time and continue to develop. It is based on experience, often treated over centuries of use, adopted to local culture and environment and is dynamic and changing